2015
DOI: 10.1530/eje-14-1069
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcome in posttraumatic pituitary deficiency: results from The Danish National Study on posttraumatic hypopituitarism

Abstract: Objective: Posttraumatic pituitary hormone deficiency is often suggested. The impact of these predominantly mild and often irreproducible deficiencies on outcome is less clear. The aim of the present study was to describe patient reported outcome in a national a priori unselected cohort of patients with traumatic brain injury (TBI) in relation to deficiencies identified upon pituitary assessment. Design and methods: We conducted a nationwide population-based cohort study. Participants were Danish patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A wide range of values (from 5 to 90%) for the prevalence of PTHP in civilians has been reported in 40-plus studies since 2000 with most finding a range of 25–50% ( 27 , 45 ). The large variance is due to differences in the populations sampled, injury severity, time since injury, hormone measurement methods, and screening and clinical diagnostic criteria ( 46 , 47 ). We employed clearly defined screening criteria calculated from the distribution of basal morning concentrations of each hormone in a reference population.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of values (from 5 to 90%) for the prevalence of PTHP in civilians has been reported in 40-plus studies since 2000 with most finding a range of 25–50% ( 27 , 45 ). The large variance is due to differences in the populations sampled, injury severity, time since injury, hormone measurement methods, and screening and clinical diagnostic criteria ( 46 , 47 ). We employed clearly defined screening criteria calculated from the distribution of basal morning concentrations of each hormone in a reference population.…”
Section: Discussionmentioning
confidence: 99%
“…Hellawell and colleagues found that 1 year after moderate or severe traumatic brain injury up to 60% of patients presented with symptoms similar to those of hypopituitarism . TBI patients are known to present with fatigue, deterioration of sex life and a feeling of social isolation, increased body fat and decreased lean body mass, and reduced muscle strength and dyslipidemia . Although referring clinicians were not endocrinologists in our series, a clinical endocrinologist had also seen the patient prior to testing, so it seems unlikely that the nonsuperiority of symptom‐based testing over random testing reflects lack of endocrine clinical acumen in the referring physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Since individuals after TBI commonly suffer from a myriad of neurological, somatic and psychiatric sequelae of the trauma, it is difficult to ascertain which of the presented clinical symptoms may also be caused or aggravated by neuroendocrine dysfunction. A recent study from a Danish group found only a very limited relationship between hormonal dysfunction and quality of life or fatigue 2.5 years (median) after TBI [7]. These controversies and the lack of established, clear-cut risk markers for posttraumatic anterior hypopituitarism may account for the fact, that routine testing for endocrine dysfunction in TBI survivors is not widely performed in clinical practice [8].…”
Section: Discussionmentioning
confidence: 99%